Transformation of Islamic Banking Branchless Based on Local Culture - Akbar Sabani; Ishak (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Islamic banking industry is a business institution in the financial sector that shows the existence of the Islamic economy in the current Indonesian economic order. This study aims to show a model for the development of branchless banking, especially Islamic banks. This study analyzes and also designs a branchless banking business model based on a literature study and also based on a qualitative analysis with a literature study approach. Based on this study, it was found that the development model of a branchless banking Islamic bank in Indonesia is more appropriate and more appropriate if it synergizes the latest technology and the local wisdom aspects which is developing in the community because it is more in line with the character and culture and geographical conditions of Indonesia. The diversity of local wisdom embraced by the Indonesian people can be a distinct advantage in the development of branchless banking Islamic banking. The results of this study also show that Islamic banking must collaborate with local economic institutions and units so that the integrated, protected and easy-to-operate design model of sharia banking can reach out widely in the community, especially in areas that are not covered by banking services so that the target for increasing Islamic banking market share can be achieved.